Post-COVID-19 syndrome in children and adolescents: what is new in approaches to the prevention and correction of psychological, neuro-vegetative and physical manifestations? - G.V. Beketova; G.P. Mozgova; N.V. Beketova (Zdorovʹe Rebenka)
The article deals with the problem of the negative effects of post-COVID-19 syndrome (PСS) on health and the quality of life of children and adolescents. The authors provided new up-to-date information related to the epidemiology, and mechanisms of PCS formation, its characteristic clinical, psychological and neuro-vegetative manifestations depending on the age of a patient, and modern approaches to the treatment and prevention using innovative vitamin and mineral complexes. The article states that the solution for this urgent medical-psychological-social problem requires further large-scale scientific research with participation of a multidisciplinary team of doctors of various specialties, psychologists and social workers in order to effectively preserve and restore health, improve the quality of life of patients with PCS and minimize economic losses at the state level.